An investigation on cutting of the MWCNTs doped composite plates by CO2 laser beam. Issue 2 (15th October 2021) - Ceritbinmez, Ferhat; Yapici, Ahmet
Abstract : Purpose: The purpose of this study is to obtain strong materials with multiwall carbon nanotubes (MWCNTs) doped and investigate laser cut of MWCNTs also find the effect of the laser cutting parameters on composite materials. Design/methodology/approach: The laminated composite plates were manufactured by using a vacuum infusion process. The mechanical properties of the composite materials produced were determined according to American Society for Testing and Materials (ASTM) D3039M, ASTM D3171, ASTM D 792 and ASTM D2583. A 130 Watts carbondioxide (CO2 ) laser cutting machine was used for drilling the two different composite plates with a thickness of 1.6–1.5 mm. Three variables were considered as process parameters including laser power (in three levels of 84.50, 104.00 and 127.40 W), cutting speed (in three levels of 4, 6, 8 mm/s) and 14 mm fixed focal position. Findings: The fibers could not be cut due to insufficient melting in the experiments performed using 84.50 and 104.00 W laser power but the cutting was successfully completed when the laser power was 127.40 W. However, as the cutting speed increased, the contact time of the laser beam with the material decreased, so the kerf decreased, but the increased laser power created a thermal effect, causing an increase in hardness around the cutting surface. This increase was lower in MWCNTs doped composites compared to pure composites. It has been found that the addition of nanoparticles to layered glass fiber composite materials played an effective role in the strength of the material and affected the CO2 laser cutting quality. Originality/value: This study is a unique study in which the CO2 laser cutting method of MWCNT-doped composite materials was investigated and the machinability without cutting errors, such as delamination, splitting, distortion and burring using the most suitable laser cutting parameters was revealed.